Processamento de linguagem natural e a Ciência da Informação: inter-relações e contribuições - Benin, Keli Rodrigues do Amaral (2023)
Introduction: In recent decades, there has been an increase in the amount of information processed, stored and made available in documents, mainly made available in the digital environment. Due to the exponential increase in the amount of information, manual manipulation of information becomes impracticable, making it necessary to use mechanisms and tools that enable automatic processing of information. The main approach to text and language analysis by computational means is called Natural Language Processing (NLP). Objective: The objective of this research is to analyze the existing interrelationships between the field of Natural Language Processing and Information Science, describing the main contributions identified. Methodology: The research is characterized as having a qualitative and exploratory approach, as it seeks to identify and describe the existing interrelationships between the field of Natural Language Processing and Information Science. As for the methodological procedures, the research can be classified as bibliographical, based on the analysis of articles published in the BRAPCI and SCOPUS Databases, in the period 2012 and 2022, which address the interrelationship between Natural Language Processing and Life Science. Information. 68 articles were selected for analysis. After selecting articles, content analysis was carried out according to the teachings of Bardin (2011), where five categories were created (Basic and Conceptual Articles, Text Preprocessing; Semantic Analysis and Text Representation; Information Extraction and Text Mining; Topic Modeling and Text Classification) that allowed for qualitative analysis. Results: After analyzing the articles, it was possible to observe the contributions of the field of Natural Language Processing to the area of Information Science, these contributions are more significant for the area of information retrieval. Regarding the area of Information Science, it contributes to the field of Natural Language Processing, with the use of ontologies, taxonomy, thesauri, dictionaries, indexing and organization and representation of information and knowledge. Likewise, the contributions of Linguistics and Terminology to the PLN were identified, with the use of linguistic analyzes and terms. Final considerations: Given this, it was possible to analyze the interrelationships of the field of Natural Language Processing with the area of Information Science, in which the two themes are able to take advantage of the techniques and specificities of the other. Given the above, Information Science can and should take advantage of the computational tools developed within the scope of NLP research, using them in the cataloging processes and then retrieval in information centers, as well as in the creation of information representation models